2016
DOI: 10.1186/s12955-016-0509-4
|View full text |Cite
|
Sign up to set email alerts
|

Does relationship satisfaction and financial aid from offspring influence the quality of life of older parents?: a longitudinal study based on findings from the Korean longitudinal study of aging, 2006–2012

Abstract: BackgroundQuality of life (QoL) in old age is of major importance because the global population is aging rapidly. Offspring support, including financial and emotional support, is important in later life and directly affects the wellbeing of elderly individuals. The aim of this study was to examine the relationship between QoL in older parents and offspring support.MethodsWe used baseline data from the 2006–2012 Korean Longitudinal Study of Aging, from 3,274 individuals aged 65 years or older. We measured the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Social class was defined in difference aspect of society, the individual factors such as wealth, educational, occupational, family background, and races were used to categorize the difference classes. While, those factors affected the quality of life in previous studies that showed that elderly who have no national pension had poor QOL level in Korea 10 . While, low wealth and low household income was a factor related with poor QOL.…”
Section: Discussionmentioning
confidence: 93%
“…Social class was defined in difference aspect of society, the individual factors such as wealth, educational, occupational, family background, and races were used to categorize the difference classes. While, those factors affected the quality of life in previous studies that showed that elderly who have no national pension had poor QOL level in Korea 10 . While, low wealth and low household income was a factor related with poor QOL.…”
Section: Discussionmentioning
confidence: 93%
“…They pointed out that the more the adult child met the parental filial expectations and provided them with filial support, the more satisfied they were with their life . These findings were further supported by Ju et al , who found that filial behaviour characterised by relationship satisfaction and financial aid from an adult child was associated with a higher quality of life in older parents. In Asian cultures, the performance of filial obligations to older parents is primarily a family matter; there is a common expectation that adult children, especially sons, will provide old age care and support which ultimately determines a higher level of subjective well‐being in older parents .…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, it is negatively associated with perceived stress, suicidal ideation, and morale . A recent prospective study found that an unsatisfactory filial support from an adult child was inversely related to the quality of life in Korean older adults . In traditional societies like Pakistan, filial support to older parents is provided by the adult child, primarily the oldest son.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, a cross-sectional study by Yunong (2012) found that filial support was significantly positively linked to subjective wellbeing of Chinese older adults. The above-mentioned studies also recognized demographical differences and found that being male, younger adults, having a higher educational level, household income and wealth were significant predictors of better quality of life (Yunong, 2012, Ju et al, 2016. Similarly, marital status and financial aid from an adult child were found to be potential buffering factors between unsatisfactory relationships and quality of life (Ju et al, 2016).…”
Section: Filial Responsibility and Elderly Subjective Wellbeingmentioning
confidence: 93%
“…Filial responsibility of adult children to their aged parents is considered as one of the fundamental practices of Eastern culture that exerts a strong impact on elderly wellbeing. Findings based on longitudinal studies indicated that filial responsibility characterized by structural and functional support from an adult child was associated with a better quality of life (Ju et al, 2016) and low moral (Takagi & Saito, 2012). In line with this, a cross-sectional study by Yunong (2012) found that filial support was significantly positively linked to subjective wellbeing of Chinese older adults.…”
Section: Filial Responsibility and Elderly Subjective Wellbeingmentioning
confidence: 99%